Identifying the missing link between training and development and organizational performance: A mediated moderation approach - Alam, Mohammad Nurul; Alotaibi, Hammad Saleh; Bhuiyan, Abul Bashar; Zulkifli, Norhayah; Turi, Jamshid Ali; Iqbal, Juman (Asian Economic and Financial Review, 2023)
This study aims to examine the effect of training and development (TD) on organizational performance (OP), the parallel mediating effects of employee engagement (EE), employee commitment (EC), and employee retention (ER). The study also empirically tests the moderating role of performance appraisal (PA). A quantitative methodology was used to analyze the cross-sectional sample data collected from 500 workers in the ready-made garment (RMG) industry in Bangladesh through a simple random sampling technique. The data was analyzed using SPSS and PLS-SEM. The results indicated a significant positive effect of TD on OP. Additionally, EC, EE, and ER were found to mediate the relationship between TD and OP. Furthermore, the study revealed that PA moderated the associations between EE and OP, and ER and OP. These findings have important implications for managers, policymakers, factory owners, government officials, and RMG employees. The insights gained from this study can also help organizations to better understand the critical role that employee engagement, commitment, and retention play in translating training and development investments into improved organizational performance.